A comprehensive assessment of heat loss mechanisms on the propagation of lean, premixed ethylene-oxygen flames in millimeter-scale tubes. (25th July 2020) - Cowart, Samuel V.; Krishnamoorthy, Gautham
Highlights: Ethylene-oxygen deflagration simulated in mm scale tubes with multi-step kinetics. Absorption coefficients estimated through add-on functions. Radiative losses reduced flame speeds by 51–73% and impacted flame front shape. Multi-step mechanisms deemed important to predict CO2 concentrations. Impact of thermal boundary conditions (isothermal/adiabatic) also significant. Abstract: Heat loss plays an important role on the flame propagation characteristics of premixed gas mixtures in small tubes. However, stringent spatial and temporal resolutions required to simulate these phenomena cause numerical investigations to resort to single-step global reaction mechanisms and ignore radiative losses. Both these restrictions are relaxed in this study where a skeletal 10-step mechanism and an optically thin radiation model are employed to study flame propagation in lean (Φ = 0.2) premixed ethylene/oxygen mixtures in millimeter-scale tubes (1 mm and 2 mm diameters). First, convergence in the spatial and temporal resolutions were ascertained and found to compare well with the characteristic reaction zone lengths and timescales determined from detailed reaction mechanisms. The accumulation of numerical errors over the simulation time frame was determined to be less than 0.06%. Radiative losses reduced the flame propagation velocities by 73% and 51% in the 1 mm diameter and 2 mm diameter tubes respectively and made the flames less concave. The flame velocities were moderately affected by the thermal boundary conditions (adiabatic versus isothermal walls). The radiant fractions were in the range 0.12–0.17. The slow CO oxidation reactions cause CO2 concentrations to be lower than those predicted from single-step mechanisms.